Impact of dietary zinc nanoparticles and probiotics on broiler health and productivity. - Alqahtani, Amera N (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study investigates the effects of dietary nano-zinc (ZnNPs), probiotics(P), and their combined use such as growth promoters, antibacterial agents, and organic antioxidants on the growth performance, carcass characteristics, blood biochemistry, meat quality, and cecal microbiota of broiler chicks. Materials and Methods: The trial was conducted from 7 to 35 days of age using a randomized complete trial design with 240 unsexed Ross 308 chicks (initial body weight 104.37 ± 0.16 gm). The chicks were allocated into four treatment groups, each containing 60 chicks, with six replicates (4×6×10). The treatments were as follows: a control group fed a standard diet and three experimental groups receiving diets supplemented with ZnNPs(3.0 cm³/kg), probiotics (P, 2.0 cm³/ kg), or a combination of ZnNPs + P (3.0 + 2.0 cm³/kg). Results: The study revealed that ZnNPs and probiotics exhibited significant antibacterial activity against harmful bacteria and mold, effectively suppressing microbial growth at concentrations ranging from 50 to 95 µg/ml. The inclusion of ZnNPs and probiotics in the diets resulted in improved growth performance, with a higher body weight compared to the control group (p < 0.05). All carcass characteristics were positively influenced by the treatments, showing significant improvements compared to the control group (p < 0.05). Furthermore, the levels of malondialdehyde (MDA) were significantly reduced in the ZnNPs and probiotics-treated groups, suggesting enhanced antioxidant activity (p < 0.05). Blood biochemical indicators, including immunoglobulin concentrations, were higher in the treated groups, pointing to an improved immune response. The meat quality of the broilers also significantly improved in terms of texture, juiciness, and tenderness. Additionally, the number of harmful cecal microorganisms decreased in the supplemented groups, leading to a healthier gut microbiota and overall improved animal health. Conclusion: The study shows that dietary supplementation with ZnNPs and probiotics has a positive impact on broiler growth, carcass traits, meat quality, blood parameters, and microbial status. These results suggest that incorporating ZnNPs and probiotics into broiler diets can be an effective strategy for enhancing productivity, meat quality, and overall health status, ultimately improving the sustainability of poultry production systems. J. Adv. Vet. Anim. Res., 12(1): 19–32, March 2025 http://doi.org/10.5455/javar.2025.l868